Research on the Layout Plan of Tether-typed Submerged Floating Tunnel. (2016) - Xiang, Jiajun; Pi, Xiaojian; Feng, Shilun; Bian, Chen
Abstract: Submerged floating tunnel as a new form of tunnel structure, has not been put into practical engineering construction, so it is necessary to conduct deep theoretical and experimental researches, and how to minimize costs while ensuring the safety of the submerged floating tunnel is a great challenge that designers face. Tether-typed(tension leg type) submerged floating tunnel is a submerged floating tunnel which suffers buoyancy greater than its weight. In the paper, under the special soil condition of the South China Sea region, the correlation of main design parameters(submerged floating tunnel length and diameter, the ratio of buoyancy and gravity, the length and space of single pile foundation) is researched based on the straight line tether-typed submerged floating tunnel with double-row single pile, single vertical tether, round section, and a series of different layout plans for tether-typed submerged floating tunnel are proposed, whose economy is evaluated from the perspective of the total amount of steel, providing reference to propose the optimal layout plan for the designers and related personnel of the tether-typed submerged floating tunnel.